(untitled) (Journal of Management and Business Education, 2019)
The purpose of this article is to analyze the relationships between learning styles and student learning strategies of two universities located in Brazil and Spain. The quantitative and descriptive study was conducted with a sample of 106 students of the last year of the course of administration and business management (BM) of both countries. The instruments for data collection were: the inventory of the learning styles of David Kolb (1984) and the learning strategies of the MSLQ (Motivated Strategies for Learning Questionnaire) of Pintrich et al. (1993). The results revealed that there are no significant differences between learning strategies and learning styles. Therefore, it cannot be affirmed that a student with a certain predominant learning style presents levels of development of learning strategies different from those of a student with another learning style. The main contribution of this article to the teaching practice is that it reveals the importance of analyzing both the learning strategies, as well as the abilities and learning styles of the students to plan teaching strategies focused on the student in order to improve their cognitive abilities and help them better manage their studies.